Evaluating the implementation of article 22 of the UN Convention on the Rights of the Child in Uganda - Nakivale Refugee Settlement: duty bearers’ and children’s voices - Alessandri, Greta (2015)
The aim of this study was to evaluate how the United Nations Convention on the Rights of the Child (CRC) article (art.) 22, has been operationalized in the Ugandan Legislation, and implemented in the local context of Nakivale Refugee Settlement. The researcher tried to comprehend specifically how the refugee children themselves perceive the implementation of CRC art.22 through their own voice. Hence, an important approach when presenting the empiric data was to provide the perspective of the child, not just to have a child perspective (i.e. an adult perspective on children's experiences). Finally, through the assessment of the children’s well-being, this study evaluated whether the anticipated goals of the mentioned legislation have been achieved in Nakivale. Data for this study were collected using qualitative methods, including: documents review, semi-structured individual interviews, focus group discussions and participant observation. The study population was primarily composed by refugee children, and secondly by staff from humanitarian organizations operating in the settlement. Ethical considerations were particularly important in this study, due to its extensive engagement with refugee children, an inherently vulnerable population. The assessment of the status quo of the life of refugee children in Nakivale reveals failure in ensuring the greatest possible implementation of art.22 by the aid workers operating in the settlement and a general feeling of hopeless and disorientation among the refugee children. The study includes recommendations to the main humanitarian institutions in charge of protection of refugee children. Overall, extraordinary efforts are urgently needed in order to guarantee refugee children of Nakivale Refugee Settlement the respect of fundamental rights and a treatment according to the internationally recognized legal standards.